Infant feeding initiation practices in the context of COVID-19 lockdown. (January 2021) - Zanardo, Vincenzo; Tortora, Domenico; Guerrini, Pietro; Garani, Gianpaolo; Severino, Lorenzo; Soldera, Gino; Straface, Gianluca
Abstract: Objective: Limited information is available regarding barriers to breastfeeding during the COVID-19 lockdown. Study design: This study was designed as a non-concurrent case-control study on breastfeeding initiation practices, defined according to WHO, in women giving birth during lockdown, between March 8 and May 18, 2020, in the COVID-19 'hotspot' in Northeastern Italy (study group), with an antecedent puerperae-matched group (control group). Exclusive, complementary, and formula feeding practices were collected from maternal charts at hospital discharge, on the second day post-partum, when puerperae filled out the Edinburg Postnatal Depression Scale (EPDS). Results: The COVID-19 study group presented significantly lower exclusive breastfeeding rates than the control group who members gave birth the previous year (−15%, p = 0.003), as a consequence of the significantly higher prevalence of complementary feeding practices in the former (+20%, p = 0.002). Conversely, the COVID-19 study group showed significantly higher EPDS scores (8.03 ± 4.88 vs. 8.03 ± 4.88, p < 0.005) and higher anhedonia (0.56 ± 0.65 vs. 0.18 ± 0.38, p < 0.001) and depression (0.62 ± 0.60 vs. 0.39 ± 0.44, <0.001) subscale scores. In the general linear model analysis, women practicing exclusive breastfeeding showed significantly lower EPDS scores in comparison with those practicing complementary (p = 0.003) and formula feedings (p = 0.001). Furthermore, the highest EPDS scores were observed in women adopting formula feeding, mainly during the COVID-19 quarantine (p = 0.019). Conclusion: This study indicates that hospital containment measures adopted during lockdown in the 'hotspot' COVID-19 epidemic area of Northeastern Italy have a detrimental effect on maternal emotions and on breastfeeding exclusivity practices. Highlights: Of the various barriers to breastfeeding, limited information is available on the COVID-19 lock down. Covid-19 lock down was associated with significantly lower exclusive breastfeeding practices. COVID-19 lock down had detrimental effect on maternal emotions and on breastfeeding exclusivity practices.